Gut microbiome compositional and functional differences between tumor and non-tumor adjacent tissues from cohorts from the US and Spain - Allali, Imane (Gut Microbes, 2015)
Colorectal cancer (CRC) is the third most common cancer in the world and the second leading cause of cancer deaths in the US and Spain. The molecular mechanisms involved in the etiology of CRC are not yet elucidated due in part to the complexity of the human gut microbiota. In this study, we compared the microbiome composition of 90 tumor and matching adjacent tissue (adjacent) from cohorts from the US and Spain by 16S rRNA amplicon sequencing in order to determine the impact of the geographic origin on the CRC microbiome. Data showed a significantly (P < 0.05) higher Phylogenetic Diversity (PD) for the US (PD Adjacent = 26.3 ± 5.3, PD Tumor = 23.3 ± 6.2) compared to the Spanish cohort (PD Adjacent = 18.9 ± 5.9, PD Tumor = 18.7 ± 6.6) while no significant differences in bacterial diversity were observed between tumor and adjacent tissues for individuals from the same country. Adjacent tissues from the Spanish cohort were enriched in Firmicutes (SP = 43.9% and US = 22.2%, P = 0.0001) and Actinobacteria (SP = 1.6% and US = 0.5%, P = 0.0018) compared to US adjacent tissues, while adjacent tissues from the US had significantly higher abundances of Fusobacteria (US = 8.1% and SP = 1.5%, P = 0.0023) and Sinergistetes (US = 0.3% and SP = 0.1%, P = 0.0097). Comparisons between tumor and adjacent tissues in each cohort identified the genus Eikenella significantly over represented in US tumors (T = 0.024% and A = 0%, P = 0.03), and the genera Fusobacterium (T = 10.4% and A = 1.5%, P = <0.0001), Bulleida (T = 0.36% and A = 0.09%, P = 0.02), Gemella (T = 1.46% and A = 0.19%, P = 0.03), Parvimonas (T = 3.14% and A = 0.86%, P = 0.03), Campylobacter (T = 0.15% and A = 0.008%, P = 0.047), and Streptococcus (T = 2.84% and A = 2.19%, P = 0.05) significantly over represented in Spanish tumors. Predicted metagenome functional content from 16S rRNA surveys showed that bacterial motility proteins and proteins involved in flagellar assembly were over represented in adjacent tissues of both cohorts, while pathways involved in fatty acid biosynthesis, the MAPK signaling pathway, and bacterial toxins were over represented in tumors. Our study suggests that microbiome compositional and functional dissimilarities by geographic location should be taken in consideration when approaching CRC therapeutic options.